2007
DOI: 10.1007/s00404-007-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of cervix cancer, human papilloma virus (HPV) and HPV vaccination at the moment of introduction of the vaccine in women in Belgium

Abstract: Upon introduction and marketing of the first HPV vaccine, only 50% of women attending a routine gynecology clinic were aware of the role of HPV in cervix cancer and the possibility of getting a vaccination against it. Unexpectedly, despite a high degree of education, young women seem to have a low awareness of cervix cancer, its cause and the preventive measures. Contrary to some women in the USA, Western European women are less likely to decline the HPV vaccine because it will protect them against STD. In Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
62
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 17 publications
13
62
4
Order By: Relevance
“…Knowledge of cervical cancer was acceptable but the level of knowledge was poor when it comes to HPV infection and the HPV vaccine. Donders et al, (2007) found among Belgian women, 50.4% answered cervical cancer is caused by virus compared to only 16.5% of our Syrian mothers who gave similar answer. However, more Syrian mothers (53.6%) said that cervical cancer is preventable compared to Belgian women (41.7%).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Knowledge of cervical cancer was acceptable but the level of knowledge was poor when it comes to HPV infection and the HPV vaccine. Donders et al, (2007) found among Belgian women, 50.4% answered cervical cancer is caused by virus compared to only 16.5% of our Syrian mothers who gave similar answer. However, more Syrian mothers (53.6%) said that cervical cancer is preventable compared to Belgian women (41.7%).…”
Section: Discussioncontrasting
confidence: 55%
“…This is also higher compared to earlier studies among Turkish (Onan et al, 2007) and rural American women (Fazekas et al, 2006). However fewer Syrian women had heard of the HPV vaccine compared to 87.5% of Belgian women who had heard of the vaccine prior to introduction of HPV vaccine in Belgium (Donders et al, 2007). These differences could be due to the difference in the way of the questions were asked.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It is of interest to note that our study was conducted approximately 2 years after the release of the HPV vaccine in our market and before the widespread media coverage. Other studies conducted on urban or a combination of urban and rural populations showed that the intention for vaccination ranged from as high as 96% [36] to as low as 50% [37]. On the whole, in studies with both urban and rural participants, the rural participants were significantly more likely to indicate a negative intention to get the HPV vaccine compared to their urban counterparts [32,38].…”
Section: Discussionmentioning
confidence: 95%